2018
DOI: 10.1097/meg.0000000000001102
|View full text |Cite
|
Sign up to set email alerts
|

Pylera and sequential therapy for first-line Helicobacter pylori eradication: a culture-based study in real clinical practice

Abstract: In our country, sequential and bismuth-based quadruple therapy achieved similarly high eradication rates as first-line treatments for H. pylori infection in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 21 publications
1
27
0
2
Order By: Relevance
“…In almost 3% of the cases, treatment was discontinued due to AEs. [16][17][18]27,[30][31][32]34,35,37,38,[42][43][44][45]47…”
Section: Safety Of Pylera ®mentioning
confidence: 99%
See 1 more Smart Citation
“…In almost 3% of the cases, treatment was discontinued due to AEs. [16][17][18]27,[30][31][32]34,35,37,38,[42][43][44][45]47…”
Section: Safety Of Pylera ®mentioning
confidence: 99%
“…Fiorini (2017b),, De Francesco (2018) andFiorini (2018) used double doses PPI (esomeprazole 20 mg bid); Gómez-Rodríguez (2017) and Rodríguez de Santiago (2017) used double dosis PPI (omeprazole 40 mg bid); Rodriguez de Santiago (2017), Perez-Arellano (2017), Gravina (2018), Tarhini (2018) and Ciccaglione (2018) used high-dosage PPI (esomeprazole 40 mg bid) and were also excluded from the sensitivity analyses. c Rodriguez de Santiago (2017), Pérez Arellano (2017), Gravina (2018), Tarhini (2018) and Ciccaglione (2018) used esomeprazole 40 mg bid.…”
mentioning
confidence: 99%
“…These results were even slightly higher than expected according to most recent studies that reported eradication rates ranging from 83% to 95% with CQT [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and from 80% to 95% with BQT. 25,[30][31][32][33][34][35][36][37][38][39] Since eradication rates of different therapies depend on the H pylori resistance pattern to antibiotics, our results are region specific and only applicable to areas with similar resistance rates to main antibiotics.…”
Section: The Addition Of Certain Probiotics (Different Lactobacillus Andmentioning
confidence: 99%
“…An Italian study comparing sequential and bismuth‐based therapy did not find that the pattern of bacterial resistance significantly affected eradication rates. Dual resistance to clarithromycin and amoxicillin did, however, lower eradication rates in both treatment strategies . Susceptibility‐based therapy is especially important to guide tailored treatment after failure of standard empiric therapies.…”
Section: Culture‐guided Treatmentmentioning
confidence: 99%
“…Dual resistance to clarithromycin and amoxicillin did, however, lower eradication rates in both treatment strategies. 62 Susceptibility-based therapy is especially important to guide tailored treatment after failure of standard empiric thera-…”
Section: Culture-g U Ided Tre Atmentmentioning
confidence: 99%